A Socio-Stylistic Analysis of Adrienne Rich’s Poem “Dividing into the Wreck” (Prithvi Academic Journal, 2025)
Women’s oppression and subjugation have been throughout human history. Rich, as a feminist, portrays the issues of gender in her poems, and attempts to recreate the women’s history and voices for women’s liberation. Stylistic analysis is significant to explore the meaning of a text. This study explores the stylistic devices in Rich’s “Diving into the Wreck” associating with the socio-cultural issue of gender injustice in the patriarchal society and women’s liberation. The study shows how linguistic and literary features of the poem present the meaning and effect. It fulfils the gap between the meaning and meaning making evidences in the analysis. This study has used a socio-stylistic analysis as the theoretical tool. The findings of the study are that stylistic devices such as allusion, enjambment, alliteration, allegory, symbols are used to make poetic effects on readers and/or people to eradicate the “myths” and redefine womanhood in modern society. The speaker of the poem encourages women to self-discovery the truth of women for the women’s rights, identity and gender justice in the modern society. Rich as the speaker of the poem rejects the false stories of history and makes a journey to dive into the ocean of the damaged history. Thus, Rich’s feminist voice depicted in her poems encourages the common women and feminists to recreate a new history for gender equality.